Judgment of pure fermented soy sauce by fluorescence resonance energy transfer of OPA-tryptophan adduct. (1st July 2015) - Gao, You-Syuan; Hsieh, Bo-Chuan; Cheng, Tzong-Jih; Chen, Richie L.C.
Highlights: A rapid, sensitive and selective tryptophan detecting method based on FRET and FIA. A data subtraction protocol proposed to eliminate the interference. The relative tryptophan content in soy sauce and the quality were estimated in minutes. Abstract: Tryptophan was detected with a flow-injection manifold after reacting with mM order of fluorogenic o -phthalaldehyde (OPA)/thiol reagent (pH 10.0) in the carrier stream (0.63 mL/min). Based on the intra-molecular fluorescence resonance energy transfer of OPA-tryptophan adduct, the difference in fluorescence intensity obtained at 280 and 300 nm excitation was used to detect tryptophan content with satisfactory precision (CV < 6.5% for concentration higher than 0.5 μM), linearity (0.1–10 μM, R 2 = 0.9893) and sensitivity (≈10 nM). Since tryptophan will decompose during manufacturing non-fermented soy sauce by acid-hydrolysis procedure, the method was used to discriminate pure fermented soy sauces, adulterated soy sauces and chemical soy sauces in less than 5 min. The ratio of tryptophan to total amino acid content served as the index for the judgment, and the results were validated by capillary electrophoresis.